2012
DOI: 10.1017/s0016774600000457
|View full text |Cite
|
Sign up to set email alerts
|

Morphodynamic development and sediment budget of the Dutch Wadden Sea over the last century

Abstract: The availability of nearly 100 years of bathymetric measurements allows the analysis of the morphodynamic evolution of the Dutch Wadden Sea under rising sea level and increasing human constraint. The historically observed roll-over mechanisms of landward barrier and coastline retreat cannot be sustained naturally due to numerous erosion control measures that have fixed the tidal basin and barrier dimensions. Nevertheless, the large continuous sedimentation in the tidal basins (nearly 600 million m 3 ), the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(150 citation statements)
references
References 41 publications
(52 reference statements)
6
144
0
Order By: Relevance
“…Observational evidence suggests that both gross and residual fluxes of sediment in the Marsdiep are much larger than in the Vlie Gerkema et al 2014). Although the Eierlandse inlet is known to be morphodynamically active (Elias et al 2012), it is believed to be the least important in terms of exchange flows, mainly because of its small size and small tidal prism when compared to the other two inlets.…”
Section: Study Sitementioning
confidence: 99%
“…Observational evidence suggests that both gross and residual fluxes of sediment in the Marsdiep are much larger than in the Vlie Gerkema et al 2014). Although the Eierlandse inlet is known to be morphodynamically active (Elias et al 2012), it is believed to be the least important in terms of exchange flows, mainly because of its small size and small tidal prism when compared to the other two inlets.…”
Section: Study Sitementioning
confidence: 99%
“…Although they are excluded from the nourishment programme these coastal areas benefit from sediment import from the coastal foundation. Recent studies on the adaption of the tidal basins of the Wadden Sea to the closure of the Zuider Zee and sand-mining, show that imported sediment volumes have been more than adequate to compensate for current SLR (Elias et al 2012) which might indicate a sediment transport capacity through the inlets that is large enough to accommodate higher rates of SLR than currently occur. An increase in yearly nourishment volume to 20 million m 3 is anticipated in the National Waterplan (MVenW 2009) but no decision has yet been made.…”
Section: Netherlandsmentioning
confidence: 99%
“…Based on the bathymetric data since around 1927 Elias et al (2012) present an evaluation of the morphological developments of the Dutch Wadden Sea. It is shown that even today, the morphology in the Western Wadden Sea is still adapting to the closure of the Zuider Sea .…”
Section: Introductionmentioning
confidence: 99%
“…An increase of the tidal prism would generally result in an increase of the ebb-tidal delta volume (Walton and Adams, 1976) and larger channels in the basin corresponding to sediment surplus. However, according to Elias et al (2003Elias et al ( , 2012, the ebb-tidal deltas of Texel and Vlie inlet are shrinking due to the sand demand in the inner parts of the basins near the closure dam. Sedimentation in the basins has taken place in the channels close to the Afsluitdijk, in the channel connecting Marsdiep (channel directly north of Den Helder) to Vlie and in the back of the Vlie basin (Fig.…”
Section: Introductionmentioning
confidence: 99%